EFEKTIVITAS PEMANFAATAN POSTER CANDI NGEMPON SEBAGAI SUMBER BELAJAR IPS DI SMP NEGERI 1 BERGAS - unnes, Safitri; Salam, Rudi (SOSIOLIUM : Jurnal Pembelajaran IPS, 2020)
This research is a research that aims to determine the level of effectiveness of the use of Ngempon Temple posters as a learning source of social science studies in SMP Negeri 1 Bergas. The method in this study is quantitative. The results of this study is that using Ngempon Temple posters as a learning sources of social science studies can be implemented effectively, by the results of students learning activities are about 9.67% are included in the sufficient criteria, 61.29% are included in the high criteria, and 29.03% are included in the very high category. The outcomes of students’ cognitive learning are high after the researcher gives a treatment, which is there are 15 students who can obtain the score of Minimum completeness criteria (KKM). The analysis of the students responses also classified in high criteria, namely 16.12% are very good, 74.19% are good, and only 9.67% are included in the sufficient criteria. Penelitian ini merupakan penelitian yang bertujuan untuk mengetahui tingkat keefektifan pemanfaatan poster Candi Ngempon sebagai sumber belajar IPS di SMP Negeri 1 Bergas. Metode dalam penelitian ini yakni kuantitatif. Hasil dari penelitian ini yaitu pemanfaatan poster Candi Ngempon sebagai sumber belajar IPS efektif diterapkan, dengan hasil aktivitas belajar peserta didik yaitu sebanyak 9,67 % termasuk dalam kriteria cukup, 61,29% termasuk dalam kriteria tinggi, dan 29,03% dalam kategori sangat tinggi. Hasil belajar kognitif peserta didik tinggi setelah diberikan treatment, yakni 15 peserta didik mampu mencapai nilai Kriteria Ketuntasan Minimal (KKM). Serta respon peserta didik yang tergolong tinggi,yaitu dengan hasil analisis respon peserta didik sebanyak 16,12% sangat baik, 74,19% baik dan hanya 9,67% yang termasuk dalam kriteria cukup.